Mycobacterium farcinogenes and Mycobacterium senegalense as new environmental threats - Jafar Aghajani; Esmaeil Rajaei; Poopak Farnia; Donya Malekshahian; Shima Seif (Biomedical and Biotechnology Research Journal, 2018)
Background: Mycobacterium farcinogenes and Mycobacterium senegalense are the causes of the bovine farcy, a chronic granulomatous disease of the skin of zebu cattle. The zoonotic potential of these bacteria is unclear. The high contamination rate of these bacteria (as species of nontuberculous mycobacteria) has been reported in environmental samples. This study aimed to determine the prevalence of these bacteria in the water and soil environment in four suburbs of Tehran, Iran. Methods: A total of 4014 soil and water samples were collected from four areas of Tehran including Robat Karim, Firuzkuh, Shahr-e-Ray, and Varamin. In each city, at least one sample was collected per 1002 m. The sediment samples were cultured on the Lowenstein–Jensen medium. Twice a week was observed to study the growth of colony, morphology, and pigmentation. Colonies were studied using phenotypic tests. Molecular analysis was also carried out on colonies. Results: Among samples, the number of collected water samples was 48.48% (1946/4014), and the number of soil samples was 51.51% (2068/4014). Results of cultures from collected samples showed that 21.47% (862/4014) of them were positive. Among the studied areas, Rabat Karim has been identified as the most polluted region (169/480; 35%). The abundance of M. farcinogenes has been dominant in Ray. The least infection has been reported in Varamin. Conclusion: The results showed that the prevalence of these two strains was very high in water and soil. Due to these two strains are the main and effective factors of bovine farcy in zebu cattle (the most farmed cows in Iran), surveillance of the zoning potential of this disease is very important.